Safety, Efficacy, and Persistence of Emtricitabine/Tenofovir Versus Other Nucleoside Analogues in Naive Subjects Aged 50 Years or Older in Spain: The TRIP Study. Issue 5 (September 2013) - Blanco, José Ramón; Caro-Murillo, Ana María; Castaño, Manuel Angel; Olalla, Julián; Domingo, Pere; Arazo, Piedad; Gómez-Sirvent, Juan Luis; Riera, Melchor; Pulido, Federico; Vera, Francisco; Romero-Palacios, Alberto; Aguirrebengoa, Koldo; et al.
Abstract : Objectives: Current antiretroviral guidelines state that being older than 50 to 55 years of age is an indication to start antiretroviral therapy (ART), regardless of CD4 status. However, no references to the preferred combination ART (cART) for these patients have been described. Our study compares emtricitabine and tenofovir disoproxil fumarate (FTC/TDF) versus other nucleoside reverse transcriptase inhibitor (NNRTI) regimens in HIV ART-naïve patients who are ≥50 years.Design: National, retrospective cohort analysis of patients who were ≥50 years old when they began the first cART (January 1, 2006 to December 31, 2009).Methods : We compared safety, effectiveness, and persistence of treatment in FTC/TDF versus non-FTC/TDF users. Among FTC/TDF users, we compared protease inhibitor (PI) versus NNRTI users and lopinavir/r versus efavirenz users.Results: We included 161 patients: median age was 54.6 years, 83% were men, median CD4 count was 191 cells/µL, median viral load was 4.7 log, and median follow-up was 19 months (maximum, 48 months). Of these participants, 112 started with FTC/TDF and 49 with other nucleotide reverse transcriptase inhibitors (NRTIs). During follow-up, 21.9% of subjects developed at least one laboratory event ≥grade 3, 5.6% interrupted cART due to adverse events, 19.3% had virologic failure, and 49.1% modified cART. There were no statistically significant differences between FTC/TDF and non-FTC/TDF users for any output except for persistence: The proportion of subjects who changed cART was 71.4% for non-FTC/TDF users and 38.6% for FTC/TDF users (log rank 0.001; adjusted hazard ratio, 2.10; 95% CI, 1.34-3.29).Conclusions: In a population of HIV-infected subjects who were ≥50 years old, our study suggests that the use of FTC/TDF is generally safe and effective, with a longer persistence as compared to other regimens.